POLA MUSIM PENANGKAPAN Sardinella fimbriata YANG DIDARATKAN DI PPN PRIGI – JAWA TIMUR - Fuad; Sari, Wahida Kartika; Harlian, Ledhyane Ika; Akbarsyah, Nora; Budiarti, Tri Wahyu (Bogor Agricultural University, 2022)
Fringe-scale sardine (Sardinella fimbriata) is one of the dominant species landed in Prigi fishing port. However, in recent years the sardine fishery management might deal with some overfishing indicators of this species . The purpose of this study was to determine the trend of catches, fluctuations in catch per unit effort (CPUE), and the pattern of the fringe-scale fishing season using catch-effort data of purse seine and gillnet landed at PPN Prigi in the period 2011-2020. The results showed that the catch fluctuated every year . CPUE has tended to increase over the last ten years but decreased in 2014 and 2020. The highest CPUE value occurred in 2019 which was 0,21kg/trip. The Peak fishing season occurs in December – March.